Improving Elementary School Students' Learning Outcomes Through the Implementation of the Discovery Learning Model - Daga, Agustinus; Malo, Mariana; Sene, Mikael (Jurnal Ilmu Pendidikan (JIP) STKIP Kusuma Negara, 2025)
This research aims to improve students' academic achievement in Catholic Religious Education. The study involved fourth-grade students of SDN Mananga Aba. The study used Classroom Action Research. Multiple-choice test questions were used as data collection instruments. Data analysis included descriptive analysis (i.e., individual completion, class completion), analysis of observation results of teacher and student activities. The results showed an increase from cycle I to II, both in the percentage of class completion (33 to 92) and the average value (63 to 85), as well as the average teacher activity (65 to 97) and students (96 to 96). These achievements indicate that discovery learning improves student learning outcomes. This increase occurred because the researcher made improvements to learning in Cycle II, especially in the teacher's ability to apply discovery learning syntax, and was supported by increased student initiative, motivation, and collaboration during the learning process. The findings of this study have important implications for teachers. They should make greater use of innovative learning models, especially discovery learning, to improve the quality of the learning process and the achievements of elementary school students in Catholic Religious Education.